Monitoring toxicity associated with parenteral sodium stibogluconate in the day-case management of returned travellers with New World cutaneous leishmaniasis [corrected]. - Emily S Wise; Margaret S Armstrong; Julie Watson; Diana N Lockwood (Public Library of Science (PLoS), 2012)
Patients with New World cutaneous leishmaniasis (NWCL) caused by Leishmania Viannia are treated with parenteral sodium stibogluconate (SbV) to reduce the risk of development of mucocutanous leishmaniasis. Our centre manages patients with NWCL on an outpatient-basis. This study was conducted to assess the safety and efficacy of this approach.We reviewed records of 67 consecutive NWCL patients, aged 17-61 years, treated as day-cases with 20 mg/kg/day SbV for up to 28 days at our UK centre. Data had been collected in a standardised format at the time of treatment using a care-record tool. Patients reported adverse-effects daily using a structured questionnaire. Blood tests and electrocardiograms were performed twice weekly to monitor for toxicity.Parenteral SbV treatment was associated with an early, significant suppression of mean lymphocyte and platelet counts. By day four of treatment, lymphocytes reduced by 0.53×10(9)/L (CI 0.29×10(9)/L to 0.76×10(9)/L, p<0.001), and platelets by 31,000/µL (CI 16,000/µL to 46,000/µL, p<0.001). SbV was further associated with significant elevation of serum alanine transaminase concentrations, with a mean peak rise of 107 iu/L by day 13 (CI 52 iu/L to 161 iu/L, p<0.001). These disturbances were temporary and did not result in adverse clinical events. Patient-described symptoms were cumulative and at three weeks of treatment, 59.6% of patients experienced myalgia and 29.8% malaise. Treatment adherence and clinical outcomes were comparable to inpatient treatment studies. A total of 1407 individual doses of SbV resulted in only 26 nights' hospital admission, a saving of 1381 bed-days compared to inpatient treatment.In specialist centres, NWCL patients aged below 65 years and without co-morbidities can be safely and effectively treated without hospital admission. This reduces the cost of treatment, and is much preferred by patients. Twice weekly blood and electrocardiographic monitoring may be surplus to requirement in clinically well, low-risk patients.